Phagocytosis‐dependent activation of a TLR9–BTK–calcineurin–NFAT pathway co‐ordinates innate immunity to Aspergillus fumigatus. Issue 3 (30th January 2015) - Herbst, Susanne; Shah, Anand; Mazon Moya, Maria; Marzola, Vanessa; Jensen, Barbara; Reed, Anna; Birrell, Mark A; Saijo, Shinobu; Mostowy, Serge; Shaunak, Sunil; Armstrong‐James, Darius
Abstract Transplant recipients on calcineurin inhibitors are at high risk of invasive fungal infection. Understanding how calcineurin inhibitors impair fungal immunity is a key priority for defining risk of infection. Here, we show that the calcineurin inhibitor tacrolimus impairs clearance of the major mould pathogen Aspergillus fumigatus from the airway, by inhibiting macrophage inflammatory responses. This leads to defective early neutrophil recruitment and fungal clearance. We confirm these findings in zebrafish, showing an evolutionarily conserved role for calcineurin signalling in neutrophil recruitment during inflammation. We find that calcineurin–NFAT activation is phagocytosis dependent and collaborates with NF‐κB for TNF‐α production. For yeast zymosan particles, activation of macrophage calcineurin–NFAT occurs via the phagocytic Dectin‐1–spleen tyrosine kinase pathway, but for A. fumigatus, activation occurs via a phagosomal TLR9‐dependent and Bruton's tyrosine kinase‐dependent signalling pathway that is independent of MyD88. We confirm the collaboration between NFAT and NF‐κB for TNF‐α production in primary alveolar macrophages. These observations identify inhibition of a newly discovered macrophage TLR9–BTK–calcineurin–NFAT signalling pathway as a key immune defect that leads to organ transplant‐related invasive aspergillosis.